1H NMR–based metabolomics reveals the antimicrobial action of oregano essential oil against Escherichia coli and Staphylococcus aureus in broth, milk, and beef. (15th February 2023) - Hao, Yuanpeng; Guo, Xiaoqi; Zhang, Wenying; Xia, Fei; Sun, Meiyu; Li, Hui; Bai, Hongtong; Cui, Hongxia; Shi, Lei
Abstract: Foodborne illnesses affect the health of human worldwide. Thus, the search for potential antimicrobial agents against foodborne pathogens is given increased attention. This study aimed to investigate the antimicrobial mechanism of oregano essential oil (OEO) against Escherichia coli and Staphylococcus aureus in Luria–Bertani (LB) broth, milk, and beef using 1 H nuclear magnetic resonance (NMR)–based metabolomics. The time-killing assay demonstrated that OEO treatment had comparable bacteriostatic and bactericidal effects on E. coli and S. aureus in LB broth and beef, whereas OEO required more time to exert its bactericidal action in milk. The inactivation effect of OEO was confirmed by the changes in the cell morphology of E. coli and S. aureus . The 1 H NMR–based metabolomics revealed that the metabolic networks of E. coli and S. aureus under OEO stress were mainly related to the amino acid metabolism and tricarboxylic acid cycle (TCA). Our study provided additional evidence to support the use of a carvacrol-rich OEO as a natural antibacterial agent and improved the fundamental understanding of the mechanisms of its antibacterial action. Highlights: The OEO inhibited the growth of E. coli and S. aureus in LB broth, milk, and beef. The changes in cell morphology contributed to the inactivation effect. The 1 H NMR–based metabolomic was used to reveal the antibacterial action. The metabolic networks were mainly related to amino acid metabolism and TCA cycle.